2012
DOI: 10.4103/0973-029x.92978
|View full text |Cite
|
Sign up to set email alerts
|

Oral pyogenic granuloma: Various concepts of etiopathogenesis

Abstract: Pyogenic granuloma or granuloma pyogenicum is a well-known oral lesion. The name pyogenic granuloma is a misnomer since the condition is not associated with pus and does not represent a granuloma histologically. Pyogenic granuloma of the oral cavity is known to involve the gingiva commonly. Extragingivally, it can occur on the lips, tongue, buccal mucosa, palate, and the like. A history of trauma is common in such sites. The etiology of the lesion is not known, though it was originally believed to be a botryom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
213
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(239 citation statements)
references
References 21 publications
10
213
0
16
Order By: Relevance
“…Hullihen in 1844, reported the first case in literature. In 1897, occurance of PG in man was first described as Botryomycosis hominis by Poneet and Dor [1,3]. The term Pyogenic granuloma or Granuloma pyogenicum was coined by Hartzell in 1904 [3].…”
Section: IIImentioning
confidence: 99%
See 4 more Smart Citations
“…Hullihen in 1844, reported the first case in literature. In 1897, occurance of PG in man was first described as Botryomycosis hominis by Poneet and Dor [1,3]. The term Pyogenic granuloma or Granuloma pyogenicum was coined by Hartzell in 1904 [3].…”
Section: IIImentioning
confidence: 99%
“…Kerr and Bhaskar et al observed various Gram +ve and Gram-ve bacilli more commonly in ulcerated lesions near the surface tan in deeper aspects suggesting contamination from oral flora. Shafer et al stated that some minor trauma to tissue provided pathway for invasion of non-specific types of microorganisms [1,3]. The tissue responds to these low virulence organisms by overzealous proliferation of a vascular type of connective tissue.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 3 more Smart Citations